Managing Employee Performance in Tourism Services: The Integrated Role of Work-Life Balance, Work-Related Stress, And Workload - I Putu Ardiana Putra; Ni Made Dwi Puspitawati; Gde Bayu Surya Parwita (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
The purpose of this study is to analyze how work-life balance, work-related stress, and workload affect employee performance at Infinity Bali Adventure. This study employs a quantitative method using a saturated sampling technique, involving all 40 employees as respondents. Data were collected through the distribution of questionnaires that had undergone reliability, validity, and classical assumption tests. The results demonstrate that work-life balance has a significant positive contribution to employee performance; that is, a better work-life balance tends to improve employee performance. Meanwhile, work-related stress and workload have a significant negative impact on employee performance, indicating that an increase in work-related stress or workload tends to reduce employee performance. Therefore, management is advised to enhance and maintain the implementation of work-life balance, as well as reduce work-related stress levels and manage workload distribution proportionally to ensure optimal employee performance.